M-Mode in grade 3 dyspneic patients assessment - Ravikanti Karthik; Yerramsetty Venu Sashank; Kumar Ranjith K.; Haward Raymond (Halo 194)
Introduction/Objective Respiratory distress is a serious condition that can develop in the critically ill or those who have significant injuries. It is often fatal, and the risk of fatality increases with age and the severity of the illness. Therefore, an early diagnosis of the conditions that cause respiratory distress is an important factor. However, it is very challenging to make an accurate diagnosis in this domain. To clinically achieve higher accuracy during the diagnostic process, our study uses motion-mode (M-MODE) echo parameters. It aims to evaluate the accuracy of the M-MODE as a rapid assessment tool for grade 3 dyspneic patients in the Emergency Department when the physician is in a dilemma regarding the causes of respiratory distress. Methods This is a retrospective observational study. The following parameters were taken into consideration: the mitral annular plane systolic excursion (MAPSE), the tricuspid annular plane systolic excursion (TAPSE), and the E-Point to Septal Separation (EPSS) for the admitted patients. The sensitivity, specificity, and accuracy of the M-mode model were analyzed, implementing the final diagnosis as the control. For analysis, this study considered 75 patients. The M-Mode parameter, along with the emergency physician clinical Gestalt (M-Mode model), was compared with the final diagnosis at discharge or death of the patient. Results For all patients, the mean values calculated for MAPSE, TAPSE, and EPSS were 13.463mm, 15.132 mm, and 9.4685 mm. The M-Mode model showed a sensitivity and specificity of 71.43 and 88.46%, respectively. The positive predictive value and negative predictive value were 92.11 and 62.16, respectively. The accuracy of the M-Mode model was 79.95%. Conclusion The M-Mode Model can be utilized as a rapid assessment tool in the Emergency Department to initiate appropriate interventions in situations when a physician is in a dilemma regarding the cause of respiratory distress.